THE DEVELOPMENT OF JUNIOR HIGH SCHOOL INQUIRY-BASED CHEMISTRY MODULE WITH PERFORMANCE-BASED ASSESSMENT - Rasmawan, Rahmat (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2018)
The learning process in the chemistry for junior high school course emphasizes the concept discovery process, so inquiry learning is one alternative solution that can be done. The purpose of this study is to develop inquiry-based chemistry for junior high school course modules along with performance assessment. This research includes development research (Research and Development) which is generally divided into three stages, namely draft development, validation, and readability test. In the development phase of the draft module, a questionnaire, observation, and documentation technique were selected, in addition to the literature review (theory and previous research). The validation stage used validation sheets and interviews. In the readability, the phase uses the module readability questionnaire. The results showed that the developed and valid SMP chemistry modules were used from the aspects of objectives to be achieved, writing approach, truth, and depth of concepts, language clarity, the suitability of inquiry models with learning stages, physical appearance and appropriateness of performance appraisal with the learning process if the module was applied. The readability test results show that students give positive responses to the module in terms of their interest in content and appearance, renewability of content, interest in solving problems, ease of understanding the content and direction of completion.